Warm-up and hamstrings stiffness, stress relaxation, flexibility, and knee proprioception in young soccer players - Satkunskiene, D.; Ardekani, M. M. Z.; Khair, R. A. M.; Kutraite, G.; Venckuniene, K.; Snieckus, A.; Kamandulis, S. (Journal of Athletic Training, 2022)
Context: Nerves or fascia may limit motion in young soccer players, thereby contributing to frequent hamstrings injuries. Nerve-gliding exercises and self-myofascial release techniques may enhance range of motion (ROM).